Performance Analysis of Synchronous Generator: A Case Study in Steam Power Plant at PT POMI Paiton Unit 7 Probolinggo, East Java, Indonesia - Ramadoni Syahputra; Andi Wahyu Nugroho; Anna Nur Nazilah Chamim; Widyasmoro Widyasmoro; Teguh Iman Prasetyo (Universitas Muhammadiyah Yogyakarta, 2018)
This paper presents performance analysis of synchronous generator: a case study in steam power plant PT POMI Paiton unit 7 Probolinggo, East Java, Indonesia. The steam power plant is the most powerful in Indonesia. The dominance of this type of power plant can be seen from statistical data that until the end of 2018 there were 48.43% of steam power plants out of the total installed capacity of national plants. Generators used in steam power plants are generally of the synchronous generator type, which in its operation always experiences dynamics from time to time as the load changes in electricity. In this study, an analysis of the performance of synchronous generators has been carried out concerning changes in electricity load. Synchronous generator performance analysis includes output voltage, active power, reactive power, power factor, and generator efficiency. The steam power plant in this study is the largest capacity power plant in Indonesia, thus providing an important role in the supply of electric power. Based on the results of the study, it has been shown that although the load dynamics that experience changes are very dynamic, the generator performance still has good performance.